Past landscapes: the dynamics of interaction between society, landscape, and culture - Haug, Annette; Käppel, Lutz; Müller, Johannes (Sidestone Press, 2018)
Past Landscapes' presents theoretical and practical attempts of scholars and scientists, who were and are active within the Kiel Graduate School?Human Development in Landscapes? (GSHDL), in order to disentangle a wide scope of research efforts on past landscapes. Landscapes are understood as products of human-environmental interaction. At the same time, they are arenas, in which societal and cultural activities as well as receptions of environments and human developments take place. Thus, environmental processes are interwoven into human constraints and advances.0This book presents theories, concepts, approaches and case studies dealing with human development in landscapes. On the one hand, it becomes evident that only an interdisciplinary approach can cover the manifold aspects of the topic. On the other hand, this also implies that the very different approaches cannot be reduced to a simplistic uniform definition of landscape. This shortcoming proves nevertheless to be an important strength. The umbrella term?landscape? proves to be highly stimulating for a large variety of different approaches.0The first part of our book deals with a number of theories and concepts, the second part is concerned with approaches to landscapes, whereas the third part introduces case studies for human development in landscapes. As intended by the GSHDL, the reader might follow our approach to delve into the multi-faceted theories, concepts and practices on past landscapes: from events, processes and structures in environmental and produced spaces to theories, concepts and practices concerning past societies
Includes bibliographical references
Keywords: Aufsatzsammlung; Geschichte; Vor- und Frühgeschichte; Landschaft